An Analysis and Comparison of Vowel Changes between the Turkish Language and the Turkmen Dialect in Aydın Aslan's National Feelings Poems: Şair Aydın Aslan’ın “Milli Duygular” Şiirlerinde Türkçe ile Türkmen Ağzı Arasındaki Ünlü Harfler Değişimlerinin Dil Özellikleri Açısından İncelenmesi ve Karşılaştırılması (Journal of the College of Languages (JCL), 2025)
This research is an analysis and comparison of vowel changes between the Turkish language and the Turkmen dialect in Aydın Aslan's poems National Feelings. The reason for choosing this topic is to study the exact written and spoken Turkmen dialect, and comparing it to the Turkish language and delving into it to uncover many of its hidden trends. It also aims to better express the poet in the Turkmen literature and introduce him to the audience. Since the Turkmen poetry touches on reality and its vocabulary is renewed according to its development, and has a history replete with authenticity, we approach poetry and qoriyat as a means of communicating ideas, advice and guidance.In this research, the introduction provides a brief overview of the Turkmen literature, as well as information on its branches. It also reveals the poet's birthplace, as he grew up and studied in Kirkuk. Then, the study of phonetics is explained, its characteristics are highlighted and linked to the letters of the Turkmen dialect, and compared with examples to the Turkish language. The poet's national feelings poems are also written, along with transcribing the original texts and making the necessary changes to letter combinations to suit the Turkmen dialect. This is because the letters differ in form, structure, and meaning. Finally, important features of the Turkmen dialect and its characteristics are highlighted.ÖzetAraştırma konusu, şair Aydın Aslan'ın "Milli Duygular" şiirinde Türk dili ile Türkmen lehçesi arasındaki ünlülerdeki değişimler açısından dilbilimsel özelliklerin incelenmesidir. Bu konuyu seçmemin nedeni, yazılı ve sözlü Türkmen lehçelerini tam bir kopya olarak incelemek, bunları Türk diliyle karşılaştırmak ve içlerine dalarak birçok gizli eğilimi ortaya çıkarmak ve keşfetmeye çalışmaktır. Ayrıca, şairi Türkmen edebiyatında daha iyi ifade etmek ve onu dinleyicilere ve edebiyat dünyasına daha iyi tanıtmaktır. Türkmen şiiri gerçeğe dokunduğu ve kelime dağarcığı gelişimine göre yenilendiği için, özgünlüklerle dolu bir geçmişi olduğu için, şiir ve dizeleri fikirleri iletmenin bir aracı olarak öğüt ve rehberlik için kullanıyorum.       Çalışmada Türkmen edebiyatına kısa bir giriş, dalları ve şairin büyüdüğü ve eğitim gördüğü doğum yeri (Kerkük) hakkında bilgiler yer aldı. Daha sonra (fonoloji) çalışması açıklandı, özellikleri vurgulandı ve Türkmen lehçesinin harflerine bağlandı, örneklerle Türk diliyle karşılaştırıldı. Şair ayrıca "Milli Duyguları" dile getiren şiirler yazdı ve şiirlerin orijinal metnini kopyaladı ve harflerin biçim, yapı ve anlam bakımından birbirinden farklı olması nedeniyle Türkmen lehçesine uyması için harfleri birleştirmede gerekli değişiklikleri yaptı. Sonuç olarak Türkmen lehçesinin önemli özellikleri ve özellikleri vurgulandı.